Using Shakespearean drama for creative writing in ESL class room: Some techniques and suggestions (Stamford Journal of English, 2013)
Stamford Journal of English; Volume 6; Page 164-176 DOI: http://dx.doi.org/10.3329/sje.v6i0.13911